1989
DOI: 10.3109/00016358909004804
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chlorhexidine supplementation in a periodontal dressing

Abstract: Most commercial periodontal dressings claiming antibacterial activity lose this activity shortly after application. Chlorhexidine (CH) is an antibacterial agent with long-term activity in the oral cavity owing to its substantiveness and slow-release properties. In a double-blind split-mouth-designed clinical trial the effect of incorporating CH acetate in periodontal dressing was tested on wound healing after gingivectomy. Eleven patients, each needing at least two gingivectomies, constituted the test panel. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…CHX can bind phosphate, which in turn can lead to the release of small amounts of Ca 2ϩ from the root canal dentin. Provided that this assumption is true, CHX might show a possible indirect effect on the removal of Ca 2ϩ by binding the phosphate (30,31). In the present study, the least decalcifying effect (except water) was obtained with CHX between the two 5-minute intervals (5-to 10-minute and 10-to 15-minute).…”
Section: Discussionmentioning
confidence: 96%
“…CHX can bind phosphate, which in turn can lead to the release of small amounts of Ca 2ϩ from the root canal dentin. Provided that this assumption is true, CHX might show a possible indirect effect on the removal of Ca 2ϩ by binding the phosphate (30,31). In the present study, the least decalcifying effect (except water) was obtained with CHX between the two 5-minute intervals (5-to 10-minute and 10-to 15-minute).…”
Section: Discussionmentioning
confidence: 96%
“…(1996),[5] Othman et al . (1989),[18] Asboe-Jorgensen et al . (1974)[19] who recorded higher bleeding scores following one week of periodontal surgery during the healing period.…”
Section: Discussionmentioning
confidence: 99%
“…chlorhexidine negatively affected fibroblast and keratinocyte proliferation in a concentration-and time-dependent manner (32)(33)(34)(35). However, only some in vivo studies (36, 37) indicated a negative effect of chlorhexidine on wound healing, while a considerable number of studies indicated the value of chlorhexidine rinses after various oral surgical procedures and a positive effect of chlorhexidine on wound healing (1,6,(38)(39)(40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%